The economic structure of the Cape Midlands and Karroo Region : a sectoral and spatial survey - Blumenfeld, Jesmond P (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 1974)
[The] region, as defined, excludes not only these metropolitan areas themselves but also the inner peripheries of their hinterlands. Thus, virtually all areas within regular (i. e. daily) commuting distance of the metropolitan centres, and all areas into which urban development in the latter might 'spill over' in the foreseeable future are excluded. In the case of Metropolitan Port Elizabeth, these exclusions are reflected in the roughly 'crescent-shaped' southern boundary of the region. The situation of the region can further be described in terms of its major physiographic features which reveal a number of factors which are also of importance for understanding and analysing the economy of the area. Intro., p. 1.
Keywords: South Africa -- Economic conditions -- 1961-1991; Regional planning -- South Africa -- Cape Province